The Service Sentiment Indicator - A Business Climate Indicator for the German Business - Related Services Sector - Ulrich Kaiser; Herbert S. Buscher (University of Konstanz, Center of Finance and Econometrics (CoFE), 1999)
No other area of the German economy has developed so emphatically in the past ten years as that of business-related services. Regardless their growing importance, business-related services still play only a minor role in official statistics. Above all, official statistics do not provide up-to-date information on the state of the business cycle of this sector. In a situation where such quantitative information is lacking, data obtained from business surveys give important guidelines to the state of this part of the economy. In this paper we show how a relieble compounded business climate indicator for busniness-related services can be constructed from both business survey and national accounts data
urn:nbn:de:bsz:352-opus-3139
Keywords: 330; Unternehmensdienstleistung; Konjunkturindikator; Geschäftsklima; Index; Deutschland